Evaluation of an efavirenz-containing regimen: an open-label, multicenter study - Hartmann, Martin; Rump, Andres; Brust, Jürgen; Schuster, Dieter; Mosthaf, Franz; Procaccianti, Maria; Klinker, Hartwig; Petzoldt, Detlef (HIV clinical trials, 2001)
Purpose: Efavirenz (EFV) has been shown to be a highly effective HIV therapy in antiretroviral-naïve patients when used with nucleoside reverse transcriptase inhibitors. Method: The study participants were 314 patients, 45 of whom had not been previously treated with any antiretroviral medication. The other patients were heavily pretreated for about 3 years (1,047 days); 34 with two nucleoside reverse transcriptase inhibitors, 147 with triple therapy, and 88 with a quadruple regimen. Results: Suppression of plasma HIV-1 RNA to <50 copies/mL and <500 copies/mL was achieved in 56% and 72% of the pretreated patients and in 82% and 91% of the naïve patients, respectively, at week 80 (intention-to-treat analysis: noncompleters = failure: 10% and 15% and 20% and 22%, respectively). The viral load reduction at week 80 was 0.7 log10 for the pretreated patients and 2.6 log10 for the naïve patients. CD4 cell counts increased from 386 to 474 cells/μL at week 80 in the pretreated group and from 264 to 431 in the naïve patients. 118 patients discontinued the treatment due to adverse events (37 patients due to nervous system symptoms and 15 patients because of exanthema). There were no AIDS-defining events in the group of antiretroviral-treated patients. Conclusion: EFV in combination with nucleoside reverse transcriptase inhibitors as antiretroviral therapy was potent and effective in reducing viral load, mainly in treating therapy-naïve patients and in preventing AIDS-defining events.
Elektronische Reproduktion der Druck-Ausgabe 14 Januar 2015
Gesehen am 24.05.2022